2017
DOI: 10.3892/etm.2017.4232
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate influences Th17/Treg lymphocyte balance by modulating Treg apoptosis and Th17 proliferation in a murine model of rheumatoid arthritis

Abstract: CD4+ regulatory T (Treg) cells and T-helper 17 (Th17) cells have been shown to have important roles in rheumatoid arthritis (RA). In our previous study, it was demonstrated that artesunate was able to alter the Treg/Th17 ratio in patients with RA; however, the underlying mechanisms remain unclear. The present study established a male Sprague Dawley (SD) rat model of type II collagen-induced arthritis (CIA). SD rats were divided into normal control, CIA model and artesunate-treated (5, 10 or 20 mg/kg/day) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…In the present study, we have confirmed results of some previous studies showing INCREASED Th17 cells frequency, as well as Th17/Treg ratio in RA patients (16)(17)(18)(19)(20)(21)(22). In contrast to our study, Penatti A et al (23) have shown that RA patients had lower frequencies of circulating CCR6+CXCR3−Th17 cells and higher frequencies of conventional CD25+ Tregs comparing to the OA patients.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we have confirmed results of some previous studies showing INCREASED Th17 cells frequency, as well as Th17/Treg ratio in RA patients (16)(17)(18)(19)(20)(21)(22). In contrast to our study, Penatti A et al (23) have shown that RA patients had lower frequencies of circulating CCR6+CXCR3−Th17 cells and higher frequencies of conventional CD25+ Tregs comparing to the OA patients.…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating evidence based on animal models has pointed to the efficacy of ARTs in RA treatment. In type II collagen-induced arthritis (CIA) in rats, artesunate treatment not only alleviated inflammation, decreased the frequency of Th17 cells and increased Treg cells in the synovium and spleen ( 17 ), but also stimulated apoptosis or autophagy in cartilage tissue and inhibited chondrocyte proliferation through the PI3K/AKT/mTOR signaling pathway ( 18 ). Moreover, artesunate exerted a suppressive effect on osteoclastogenesis and improved arthritic bone erosion in CIA rats via inhibiting the production of ROS and activating antioxidant enzyme as well as p62/Nrf2 signaling ( 19 ).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Artemisinin significantly potentiated apoptosis and impaired ROS production in inflammatory‐related diseases 65 . Studies have revealed that artesunate and DC32, a dihydroartemisinin derivative, could reduce footpad swelling and lymphocytic infiltration in collagen‐induced arthritis (CIA) mice by restoring the balance of Treg/T‐helper 17 (Th17) and inhibiting the expression of IL‐6 or IL‐17 66,67 . Besides this, DC32 could significantly activate the Nrf2/HO‐1 signaling pathway and induce p62 transcription in CIA mice 68 .…”
Section: Anti‐inflammatory Actions Of Artemisininsmentioning
confidence: 99%